Comparison of the effect of two educational methods on academic advisors knowledge attitude and practice in Hamadan University of Medical Sciences - Seyyed Mohammad Mehdi Hazavehie; Yadollah Fathi (Strides in Development of Medical Education, 2005)
Background: According to the educational policy and regulation offering academic advising to the students is one of the essential faculty members responsibilities and medical universities must guide the students during their education in order to prevent any academic problems and barriers and improve academic achievement Objective: To Compare the effect of two educational methods on academic advisors knowledge attitude and practice Methods: Eightyseven advisors participated in this experimental study The participants were randomly divided into two groups The first group (N=43) receiving selflearning educational materials participated in a oneday workshop The second group only received selflearning educational materials A reliable and valid questionnaire was distributed to gather data Results: The findings indicated the knowledge of the advisors about advising and counselling in the first group ( =1477 SD=31) was higher than the advisors in the second group ( =1154 SD=276) so that a significant difference was observed between the two groups (P